1984
DOI: 10.3382/ps.0631833
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Zeolites in the Diet of Broiler Chickens

Abstract: Two experiments were conducted in which zeolites were added to broiler diets at the 1% level beginning at 21 days of age. In one study, diets with different energy levels were used to determine if an interaction existed between zeolite supplementation and nutrient density. No beneficial effects of zeolite supplementation on body weights were observed in either experiment. There were no statistically significant differences in feed utilization between diets with and without zeolites, and the numerical differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 3 publications
0
6
1
Order By: Relevance
“…Clinoptilolites have been reported to improve the performance of poultry (Nakaue et al, 1981;Willis et al, 1982;Waldroup et al, 1984;Olver, 1989). In the laying hen experiment reported in the present study, there was no improvement in performance with dietary supplementation with NZ.…”
Section: Discussioncontrasting
confidence: 78%
“…Clinoptilolites have been reported to improve the performance of poultry (Nakaue et al, 1981;Willis et al, 1982;Waldroup et al, 1984;Olver, 1989). In the laying hen experiment reported in the present study, there was no improvement in performance with dietary supplementation with NZ.…”
Section: Discussioncontrasting
confidence: 78%
“…Zeolites are crystalline, hydrated aluminotectosilicates of alkali and alkaline-earth cations, having infinite, three-dimensional structures of interconnecting channels and great pores, capable of trapping molecules in suitable conditions (Mumpton and Fishman, 1977;Mumpton, 1999). Also, the beneficial effects of zeolite may be attributed to the aluminum, silicon, or sodium content of zeolites, because it has been established that these minerals can influence calcium -metabolism, thus improving calcium (Ca) and phosphorus (P) utilization (Waldroup et al, 1984;Leach et al, 1990;Elliot and Edwards, 1991;Watkins andSouthern, 1991 andShariatmadahari, 2008). Studies have revealed that the zeolite (clinoptilolite) is able to adsorb damaging toxins that can reduce the growth of animals (Oğuz and Kurtoğlu, 2000), affects gut morphology, decreases pH and lowers pathogenic bacteria counts, which suggests that intestinal health can be enhanced by its use (Khambualai et al, 119 2009 andWu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Among many properties attributed to zeolites, most typically related to their effectiveness in animal nutrition is their ability to selectively exchange a variety of cations without much major changes in their structure (Waldroup et al, 1984;Elliot and Edwards, 1991;Shariatmadari, 2008). Beneficial effects may also be attributed to the silicon (Si), aluminum (Al) or sodium (Na) content of zeolites because it has been established that these minerals can influence calcium (Ca)-metabolism, thus improving Ca and phosphorus (P) utilisation (Leach et al, 1990;Watkins and Southern, 1991).…”
Section: Introductionmentioning
confidence: 99%